Systemic Radiopharmaceutical Agents (Sm-153) may be Dangerous in Hepatacellular Carcinoma - Onur Keskin; Cigdem Soydal; Xheni Deda; Bengu Manti; Ali Tuzun (World Journal of Nuclear Medicine)
Palliation of bone metastases in hepatocellular carcinoma (HCC) is sometimes difficult. Systemic pharmaceuticals have been successfully used for the palliation of bone metastasis for many years. Safety of these agents in HCC is not known completely. We presented a male patient with decompensated liver cirrhosis with HCC. Multifocal bone metastases developed in this patient and he had refractory bone pain. We treated this patient with Sm-153 (samarium) after obtaining patient′s consent. Two days after treatment, he experienced dyspnea and we detected a massive hemorrhagic pericardial effusion. He died due to this unexpected bleeding. We should use this radiopharmaceutical treatment cautiously in these cytopenic cirrhotic patients.